Assessment of Periodontal Status in Patients with Oral Lesions - A Retrospective Study in South Indian Population - Subasree Soundarajan1 , Priya lochana Gajendran2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Oral potentially malignant disorders (OPMD) are defined as the risk of malignancy being present in a lesionor condition either at the time of initial diagnosis or at a future date. They have the potential to undergomalignant transformation.Some of the potentially malignant disorders that are related to oral squamous cellcarcinoma are Oral submucous fibrosis (OSMF), Leukoplakia, Erythroplakia, & Lichen Planus. There isa dual relationship between Oral carcinoma and periodontitis.Oral lesions may have an indirect effect oninitiating periodontitis. Periodontitis can be considered as one of the risk factors for the development of oralcancer. The aim of the study is to assess the periodontal status of patients who are diagnosed with oral lesionsin Saveetha Institute of Medical & Technical Sciences (SIMATS). This is a retrospective study, carried outby analysis of the patient records from June 2019 to March 2020 were assessed. Parameters assessed were- Age, Sex, Systemic status, Periodontal parameters (Periodontal probing depth - PPD, Loss of Attachment -LOA, Bleeding on Probing - BOP), periodontal status (Healthy gingiva, Gingivits, Periodontitis) & Severityof periodontitis (Mild, moderate & severe). Data was analysed using SPSS version 23.0. Chi square test wasdone to compare the differences in proportion. A total of 192 subjects were included in the study. 93 patients(48.4%) were diagnosed with OSMF, whereas 99 patients (51.6%) were diagnosed with Leukoplakia. Malesconstituted 93.75% of the study population and females constituted 6.25% of the study population. Agegroup of the study population ranged from 20 years to 80 years. Mean age of the study population is 42.25years. 51.04% of the patients were diagnosed with gingivitis, 43.23% of the patients were diagnosed withperiodontitis & 5.73% of the patients had healthy gingiva. Chi square test results showed statisticallysignificant association between oral lesions and habits, with a p value of 0.000. Leukoplakia was found tobe more prevalent among smokers & OSMF was found to be more prevalent among patients who had thehabit of chewing Areca nut, Hans, Mawa and Pan. However, there was no statistically significant differencebetween oral lesions based on periodontal status & severity of periodontitis.Oral lesions can be consideredas an attributing factor for development of periodontitis.